The Role of Tourism in Empowering Women in Rural India (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Tourism has the potential to empower women in rural India by providing them with economic opportunities, access to education and training, and a platform to showcase their talents and skills. This research paper explores the role of tourism in empowering women in rural India through a comprehensive analysis of the various ways in which tourism can benefit women in these communities. The paper also discusses the challenges and barriers that women face in accessing and benefiting from tourism opportunities, and provides recommendations for how these challenges can be addressed to promote gender equality and women's empowerment in rural India. Tourism can also provide women in rural India with access to education and training, which can help them to improve their skills and knowledge and increase their earning potential. Many tourism projects in rural India include training programs for women in areas such as hospitality, cooking, handicrafts, and guiding, which can help them to secure employment in the tourism industry or start their own businesses. Education and training can also help women to improve their self-confidence and decision-making skills, and enable them to take on leadership roles in their communities.